Vehicular Ad Hoc Networks: Architectures, Research Issues, Methodologies, Challenges, and Trends. (31st August 2015) - Liang, Wenshuang; Li, Zhuorong; Zhang, Hongyang; Wang, Shenling; Bie, Rongfang
Vehicular ad hoc networks (VANETs) have been quite a hot research area in the last few years. Due to their unique characteristics such as high dynamic topology and predictable mobility, VANETs attract so much attention of both academia and industry. In this paper, we provide an overview of the main aspects of VANETs from a research perspective. This paper starts with the basic architecture of networks, then discusses three popular research issues and general research methods, and ends up with the analysis on challenges and future trends of VANETs.